Setting Up the Speech Production Network: How Oscillations Contribute to Lateralized Information Routing - Gehrig, Johannes; Wibral, Michael; Arnold, Christiane; Kell, Christian A. (Frontiers in Psychology, 2012)
Speech production involves widely distributed brain regions. This study focuses on the spectro-temporal dynamics that contribute to the setup of this network. 26 participants performed a cue-target reading paradigm during MEG. We analyzed local oscillations during preparation for overt and covert reading in the time-frequency domain and localized sources using beamforming. Network dynamics were studied by comparing different dynamic causal models of beta phase coupling. While a broadband low frequency effect was found for any task preparation in bilateral prefrontal cortices, preparation for overt speech production was specifically associated with left-lateralized alpha and beta suppression in temporal cortices and beta suppression in motor-related brain regions. Beta phase coupling in the entire network was modulated by anticipation of overt reading. We propose that the cognitive processes underlying the intention to speak group brain regions belonging to the speech production network by means of beta synchronization and prepare the network for left-lateralized routing of information by suppression of inhibitory alpha and beta oscillations.